2011
DOI: 10.1111/j.1600-0404.2011.01528.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of T cell subsets in ALS: a systemic immune activation?

Abstract: Our results suggest a systemic immune activation in patients with ALS. The high production of CD8(+) T and NKT cells may suggest an immunological reaction to some unknown or undetected endogenous proteins or viruses. A probably dual (neurodestructive or neuroprotective) inflammatory function of Treg cells cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 33 publications
5
92
0
Order By: Relevance
“…Henkel et al [133] demonstrated that in patients with rapidly progressing clinical states, an inverse correlation was seen between Treg numbers in the blood and leukocyte levels of FoxP3, a transcription factor required for Treg suppressive function [134]. In a second cohort of patients with ALS, the decreased cell numbers and decreased FoxP3 expression were 80 % sensitive in predicting rapid progression in patients with ALS.…”
Section: Neuroinflammation In Patients With Als: Tregsmentioning
confidence: 99%
“…Henkel et al [133] demonstrated that in patients with rapidly progressing clinical states, an inverse correlation was seen between Treg numbers in the blood and leukocyte levels of FoxP3, a transcription factor required for Treg suppressive function [134]. In a second cohort of patients with ALS, the decreased cell numbers and decreased FoxP3 expression were 80 % sensitive in predicting rapid progression in patients with ALS.…”
Section: Neuroinflammation In Patients With Als: Tregsmentioning
confidence: 99%
“…Low T cells numbers and decreased proliferative capacity in T cells are found in the blood of ALS patients (Holmoy et al, 2008). As concerned CD8+ and natural killer T cells, they were found increased in ALS patients compared to control cohort (Rentzos et al, 2011). Interestingly, ALS patients showed a reduction of CD4+/CD25+ regulatory T cells that are known to interact with the local microglia, reinforcing the hypothesis of the involvement of the adaptive immune system associated with neuroinflammatory process in ALS (Mantovani et al, 2009).…”
Section: Adaptive Immune Systemmentioning
confidence: 50%
“…An in-depth autopsy of six ALS patients reveals an enrichment of T-cell receptor Vβ2 positive T cells in the spinal cord and CSF, suggesting an antigen-driven T cell selection [150]. Finally, ALS patients with a more rapidly progressing pathology show decreased numbers of regulatory T lymphocytes (Tregs), suggesting that the numbers of Tregs are inversely correlated with disease progression [144,151]. Tregs secrete anti-inflammatory cytokines such as IL-4, IL-10 and transforming growth factor beta (TGF-β) as well as the neurotrophic growth factors glial-derived neurotrophic factor (GDNF) and BDNF.…”
Section: Pathological Phenotype Of the Immune System In Alsmentioning
confidence: 98%
“…Presence of a systemic immune activation is suggested by abnormalities observed in the blood and CSF of ALS patients such as increased numbers of circulating lymphocytes (CD4+ helper T cells, CD8+ cytotoxic T lymphocytes (CTL) and natural killer (NK) cells), increased expression of MHC class II molecules on monocytes as well as higher levels of inflammatory chemokines and cytokines (regulated on activation normal T cell expressed and secreted (RANTES), monocyte chemotactic protein (MCP-1), IL-12, IL-15, IL-17 and IL-23) [142][143][144][145][146]. Further, post-mortem studies of brain and spinal cord from ALS patients show that the activation and proliferation of microglia is associated with an infiltration of activated macrophages, mast cells and T lymphocytes which are found in close proximity to degenerating tissues [147][148][149].…”
Section: Pathological Phenotype Of the Immune System In Alsmentioning
confidence: 99%
See 1 more Smart Citation